(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the socio-political issues of the activities of the Naqshbandiya order based on the work of Yakub Charkhi "Risola dar manokib va aqaid", which is first translated into Uzbek and philosophically analyzed. And also, the article socio-philosophically explores the ideas, thoughts and proposals of the rulers to improve public administration, put forward by Yakub Charkhi.